2022
DOI: 10.5755/j02.ms.27438
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation Behavior of New Martensitic Heat-Resistant Steel

Abstract: The research focuses on the high temperature oxidation resistance of martensitic heat-resistant steel. A new type of martensitic heat-resistant steel was developed with the addition of Al and Cu, and the oxidation behavior of the new martensitic heat-resistant steel at 650 °C and 700 °C was analyzed. The high temperature oxidation kinetics curves of new martensitic heat-resistant steel at 650 °C and 700 °C were determined and plotted by cyclic oxidation experiment and discontinuous weighing method. XRD techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The parabolic rate law was assumed for the sake of simplicity, and the approximate parabolic rate constants k ″ (oxidation constant) of the two test steels were calculated from Figure 2 using the equation: Δ W 2 = k ″ t where Δ W is the weight gain per unit area (mg·cm −2 ), and t is the oxidation time (h) [ 27 ]. The derived k ″ values are shown in Figure 3 with those from previous studies [ 28 , 29 , 30 , 31 ]. As shown in Figure 3 , the oxidation constant k ″ gradually increases as the oxidation temperature rises, indicating a gradual decrease in oxidation resistance with increasing temperature.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The parabolic rate law was assumed for the sake of simplicity, and the approximate parabolic rate constants k ″ (oxidation constant) of the two test steels were calculated from Figure 2 using the equation: Δ W 2 = k ″ t where Δ W is the weight gain per unit area (mg·cm −2 ), and t is the oxidation time (h) [ 27 ]. The derived k ″ values are shown in Figure 3 with those from previous studies [ 28 , 29 , 30 , 31 ]. As shown in Figure 3 , the oxidation constant k ″ gradually increases as the oxidation temperature rises, indicating a gradual decrease in oxidation resistance with increasing temperature.…”
Section: Resultsmentioning
confidence: 54%
“… Parabolic rate constants k” of oxidation of two hot-work die steels at 600 °C. The other k” values of hot-work steels were reported by Tilen [ 28 , 29 ], Ziming [ 30 ], and Hong [ 31 ]. …”
Section: Figurementioning
confidence: 73%
“…In the case of an oxidation temperature of 650 • C, Co oxide was identified. As the authors stated in the paper [47] concerning the different intensity of diffraction peaks in XRD patterns, it was found that the oxidation of the materials was accelerated with the increase in experimental temperature. To identify the phases present in the oxidation products, an XRD analysis was also performed on the oxidized surface of the MarBN steel after 3000 h exposure in a mixed environment at a temperature of 650 °C (Figure 10).…”
Section: Xrd Phase Analysis Of the Oxide Layer At 650 • Cmentioning
confidence: 86%
“…In the case of an oxidation temperature of 650 °C, Co oxide was identified. As the authors stated in the paper [47] concerning the different intensity of diffraction peaks in XRD patterns, it was found that the oxidation of the materials was accelerated with the increase in experimental temperature.…”
Section: Xrd Phase Analysis Of the Oxide Layer At 650 • Cmentioning
confidence: 86%